Usability of planted mangroves in the coastal area of Semarang, Indonesia, as the source of secondary metabolite extracts (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hastuti ED, Izzati M, Darmanti S. 2023. Usability of planted mangroves in the coastal area of Semarang, Indonesia, as the source of secondary metabolite extracts. Biodiversitas 24: 2409-2415. Mangrove plants are a potential source of secondary metabolites. So the secondary metabolites from mangrove plants must be assessed to promote their utilization. Considering this, the present study was carried out to analyze the alkaloid and phenol content in mangrove species in Tugu District, Semarang City, Central Java, Indonesia. Alkaloid and phenol content in five mangrove species (Avicennia marina, Bruguiera gymnorrhiza, Rhizophora mucronata, Sonneratia alba, and Xylocarpus moluccensis) were estimated using the spectrophotometry method. The study results revealed that the alkaloid content of A. marina was highest (0.23 ± 0.11%), while the highest concentration of phenol content was found in X. moluccensis (9.66 ± 1.36%). However, after including the other parameters, viz., abundance Index and accessibility Index, A. marina, was found to be a potential source of alkaloid extract, and R. mucronata was a potential source of phenol extract.